Haemophilus parasuis Infection Disrupts Adherens Junctions and Initializes EMT Dependent on Canonical Wnt/β-Catenin Signaling Pathway - Hua, Kexin; Li, Yangjie; Zhou, Hufeng; Hu, Xueying; Chen, Yushan; He, Rongrong; Luo, Rui; Zhou, Rui; Bi, Dingren; Jin, Hui (Frontiers in Cellular and Infection Microbiology, 2018)
In this study, animal experimentation verified that the canonical Wnt/β-catenin signaling pathway was activated under a reduced activity of p-β-catenin (Ser33/37/Thr41) and an increased accumulation of β-catenin in the lungs and kidneys of pigs infected with a highly virulent strain of H. parasuis. In PK-15 and NPTr cells, it was also confirmed that infection with a high-virulence strain of H. parasuis induced cytoplasmic accumulation and nuclear translocation of β-catenin. H. parasuis infection caused a sharp degradation of E-cadherin and an increase of the epithelial cell monolayer permeability, as well as a broken interaction between β-catenin and E-cadherin dependent on Wnt/β-catenin signaling pathway. Moreover, Wnt/β-catenin signaling pathway also contributed to the initiation of epithelial-mesenchymal transition (EMT) during high-virulence strain of H. parasuis infection with expression changes of epithelial/mesenchymal markers, increased migratory capabilities as well as the morphologically spindle-like switch in PK-15 and NPTr cells. Therefore, we originally speculated that H. parasuis infection activates the canonical Wnt/β-catenin signaling pathway leading to a disruption of the epithelial barrier, altering cell structure and increasing cell migration, which results in severe acute systemic infection characterized by fibrinous polyserositis during H. parasuis infection.